Brake induced vibration in mountain bikes - Redfield, R. C. (The Engineering of sport 7, Volume 1, 2008)
Mountain biking design continues to evolve towards more sophisticated systems including frame structures, Suspension strategies, and braking components. Frames become lighter with directionally designed stiffness. Suspensions are designed and tuned to respond to diverse riding scenarios including large and small bump compliance, high and low speed compression and rebound damping, and pedal feedback/suspension bob. Braking components are getting more powerful, with better modulation, while maintaining stiffness and weight character. As structures become lighter and brakes become stronger, interactions between the stick-slip friction of brake pads and rotors and the stiffness of rear frame structures sometimes induce limit-cycle vibration that can be transmitted throughout much of the bicycle frame. This annoying vibration can be felt and heard and is more often seen in relatively compliant frame structures with powerful, state-of-the-art disk brakes. This paper examines the dynamic causes of these vibrations and relates them to design and operational Parameters. Kinetic versus static friction, structural stiffness and damping, brake power and modulation rate, and bike speed and brake geometry are all key contributors to the phenomenon. Specific relationships between these parameters that preclude the onset or continuance of this vibration are determined.